McMAC: A Parallel Rendezvous Multi-Channel MAC Protocol - Hoi-Sheung; So, W.; Walrand, J.; Jeonghoon Mo (2007 IEEE Wireless Communications and Networking Conference, 2007)
Many multiple channel MAC protocols for wireless networks have been proposed to make efficient use of multiple channels where each node has a single radio which allows it to send or receive on one channel at a time. However, most of the proposed protocols are single rendezvous protocols that are subject to the congestion of the control channel. The paper proposed a new parallel rendezvous protocol, McMAC, to avoid control channel congestion so that it can scale to use a large number of channels efficiently. The authors validate the protocol design using simulation and implementation.